2010
DOI: 10.4103/0972-2327.74203
|View full text |Cite
|
Sign up to set email alerts
|

Normobaric oxygen therapy in acute ischemic stroke: A pilot study in Indian patients

Abstract: Purpose:Clinical and radiological assessment of effects of normobaric high-flow oxygen therapy in patients with acute ischemic stroke (AIS).Materials and Methods:Patients with anterior circulation ischemic strokes presenting within 12 h of onset, ineligible for intravenous thrombolysis, an National Institute of Health Stroke Scale (NIHSS) score of >4, a mean transit time (MTT) lesion larger than diffusion-weighted image (DWI) (perfusiondiffusion mismatch), and an evidence of cortical hypoperfusion on magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 9 publications
1
56
0
Order By: Relevance
“…A small randomised trial of high-concentration oxygen therapy (10 L/min) in non-hypoxaemic patients (n=40) showed no clinical benefit339 and a study of very high-flow oxygen (45 L/min) was terminated in 2009 after enrolling 85 patients because of excess mortality in the hyperoxaemia group (40% vs 17%), the full report had not yet been published when this guideline was prepared 340. Finally, an observational study reported increased mortality associated with hyperoxaemia in ventilated patients with stroke on ICUs 341…”
Section: Section 8: Emergency Oxygen Use In Hospital Settingsmentioning
confidence: 99%
“…A small randomised trial of high-concentration oxygen therapy (10 L/min) in non-hypoxaemic patients (n=40) showed no clinical benefit339 and a study of very high-flow oxygen (45 L/min) was terminated in 2009 after enrolling 85 patients because of excess mortality in the hyperoxaemia group (40% vs 17%), the full report had not yet been published when this guideline was prepared 340. Finally, an observational study reported increased mortality associated with hyperoxaemia in ventilated patients with stroke on ICUs 341…”
Section: Section 8: Emergency Oxygen Use In Hospital Settingsmentioning
confidence: 99%
“…After enrolment of 85 patients, the study was terminated early due to an imbalance of deaths favouring the control arm, though it is noted that the excess in mortality in the treatment group was not considered related to the treatment by an external blinded assessor. An Indian study [81] enrolled 40 patients within 12 h of an acute anterior circulation ischaemic stroke and a National Institute Stroke Scale of more than 4 to receive either 10 L/min for 12 h via face mask in the treatment group versus room air or 2 L/min to keep oxygen saturation above 95%. There was no significant difference in NIHSS, modified Rankin or Barthel index scores between the two groups.…”
Section: Oxygen Therapy For Acute Strokementioning
confidence: 99%
“…No benefit, decreased survival, better neurological recovery as well as transient improvement of clinical function have all been reported to be associated with administration of supplemental oxygen. [35][36][37] There are no data specific to management of ventilation and end-tidal CO2 under GA for endovascular treatment of AIS. Existing data in stroke patients suggest that hypocapnia is associated with poor prognosis in stroke.…”
Section: Management Of Oxygenation and Ventilation During Endovasculamentioning
confidence: 99%